2019
DOI: 10.1007/s11047-019-09769-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid BPSO–SCA approach for feature selection

Abstract: Nature is a great source of inspiration for solving complex problems in real-world. In this paper, a hybrid nature-inspired algorithm is proposed for feature selection problem. Traditionally, the real-world datasets contain all kinds of features informative as well as non-informative. These features not only increase computational complexity of the underlying algorithm but also deteriorate its performance. Hence, there an urgent need of feature selection method that select an informative subset of features fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
(53 reference statements)
0
25
0
Order By: Relevance
“…SCA-PSO was also applied to solve object track as a real thoughtprovoking case study and results demonstrated that SCA-PSO gives better capability to track an object when compared to other trackers such as Mean-shift (MS), PF, PSO, BA, SCA, Hybrid GSA (HGSA). Kumar and Bharti (2019) proposed a hybrid method (HBPSOSCA) based on the hybridization of SCA with binary Binary PSO for feature selection problem. A cross breed approach of binary PSO was used to enhance the convergence performance of SCA.…”
Section: Hybridization With Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…SCA-PSO was also applied to solve object track as a real thoughtprovoking case study and results demonstrated that SCA-PSO gives better capability to track an object when compared to other trackers such as Mean-shift (MS), PF, PSO, BA, SCA, Hybrid GSA (HGSA). Kumar and Bharti (2019) proposed a hybrid method (HBPSOSCA) based on the hybridization of SCA with binary Binary PSO for feature selection problem. A cross breed approach of binary PSO was used to enhance the convergence performance of SCA.…”
Section: Hybridization With Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…For different α values, different performance is noticed. When α is high, classification performance is high [33]. Outputs of NSfsMI are described using two datasets that contain elements of a small number and obtain less classification error rate than using all features.…”
Section: 6mentioning
confidence: 99%
“…The most common evaluation measures employed in the text clustering domain are accuracy, purity, entropy, precision, recall, and F-measure [91,95,96]. The text clustering method produces two sets of evaluation measures, namely, internal and external measures [78].…”
Section: Evaluation Measuresmentioning
confidence: 99%